The relationship between self-reported antipsychotics side effects and depression in Saudi Arabia - Yazed AlRuthia (Elsevier, 2024)
Background: The utilization rate of antipsychotics to treat different mental disorders is rising. However, little is known about their side effects' impact on depression levels. Therefore, the objective of this study was to examine the association between antipsychotic side effects and depression among psychiatric patients treated with antipsychotics. Methods: This is a prospective, single-center, interview-based, cross-sectional study that examined the association between antipsychotic side effects and depression among adult patients (e.g., ≥18 yrs.) with psychiatric illnesses (e.g., depression, schizophrenia, bipolar disorder) visiting outpatient clinics in a university-affiliated tertiary care center. Antipsychotic side effects were assessed using the Arabic version of the Glasgow Antipsychotic Side-effect Scale (GASS), while depression was assessed using the Arabic version of the 9-item Patient Health Questionnaire (PHQ-9). Univariate and multiple linear regressions were conducted to examine the association between the PHQ-9 and GASS scores. Results: One hundred patients met the inclusion criteria and consented to participate. Most of the patients were females (72 %) with a mean age of 38 years. Schizophrenia (37 %) and bipolar disorder (54 %) were the most common mental disorders among the recruited patients. The majority of patients were treated with atypical (e.g., second-generation) antipsychotics (88 %) for at least six months (74 %). Controlling for age, gender, annual family income, education, employment status, marital status, number of comorbidities, duration of treatment with antipsychotics, the type of antipsychotic, and psychiatric illness, higher GASS scores, which indicate more severe antipsychotic side effects, predicted higher PHQ-9 score (e.g., higher levels of depression) (β = 0.419, 95 % CI=[0.307-0.532], p-value < 0.0001). Conclusion: Early identification and management of antipsychotic side effects among psychiatric patients should enhance patient adherence and improve treatment outcomes. Future studies should verify the findings of this study using more robust study designs.